The Influence Of The Perception Of Business Actors About Accounting, Accounting Knowledge And Business Scale On The Use Of Accounting Information For MSMEs In The Special Region Of Yogyakarta - Daffa, Muhammad; Nurkhin, Ahmad; Aziza, Maghfira Nur; Wedadjati, Ratna Sesotya (Jurnal Ekonomi, 2024)
The Indonesian government recognizes the importance of Micro, Small and Medium Enterprises (MSMEs) in reducing poverty and improving national economic well-being. As an economic development strategy, the empowerment of MSMEs is considered important for regional and national economic growth. The focus of this study was to evaluate how the perception of MSMEs about accounting, accounting knowledge and business scale affect the use of accounting information in the Special Region of Yogyakarta (DIY) with a total of about 324,000 MSMEs. The methodology of this study is quantitative, using a survey with a sample of 106 respondents through purposive sampling techniques from the MSME population in DIY. Data were collected through questionnaires and analyzed using SPSS version 25 to perform descriptive analysis, classical assumption test and multiple regression (t test and partial coefficient of determination). The results showed that accounting knowledge and business scale significantly influenced the use of accounting information by MSMEs, while perceptions of accounting did not. Accounting knowledge has a strong positive influence with a significance value of 0.370 (p<0.05), confirming the need to improve understanding of accounting among MSMEs. The scale of the business also had a positive effect with a significance value of 0.044 (p<0.05), indicating that the larger the business, the more likely it is to use accounting information effectively. On the other hand, perceptions of accounting showed no significant influence with a significance value of 0.743 (p>0.05), suggesting that attitudes towards accounting may be less relevant than factual knowledge. In conclusion, MSMEs in DIY must improve accounting knowledge to utilize accounting information more effectively, supporting growth and business continuity. Government and consultants are advised to provide training aimed at improving accounting knowledge. Future studies may broaden the scope by including other variables such as the education of business actors, the age of the company, and good governance practices for a more comprehensive and in-depth analysis.